Acute Pancreatitis severity scoring index: Prospective study to identify determinants in Pakistan - Tanveer Hussain , Muhammad Hanif , Ramlah Ghazanfor , Sarmad Arslan , Ibia Nawaz , Muhammad Umar, Tanveer Hussain , Muhammad Hanif , Ramlah Ghazanfor , Sarmad Arslan , Ibia Nawaz , Muhammad Umar (Journal of Rawalpindi Medical College, 2020)
Introduction: The purpose of the study was to compare different parameters used in Ranson’s Criteria, Bedside Index of Severity in Acute Pancreatitis (BISAP), Acute Physiology and Chronic Health Evaluation (APACHE-II), and modified computed tomography severity index (MCTSI) for predicting the severity of acute pancreatitis and formulate a new scoring system to assess the severity of acute pancreatitis based on their prognostic severity index in the local population. Materials and Methods: This prospective pilot study was conducted at Rawalpindi Medical University allied hospitals from August 2019 to December 2019. All patients with a diagnosis of acute pancreatitis were included in the study through non-probability convenient sampling. Different scoring parameters were entered into standardized proforma. Results: 100 patients were included in the pilot study with a mean age of 46.53 ± 15.324. Among 24 parameters from APACHE-II, Ranson’s, BISAP, and MCTSI, only 11 parameters, Pleural effusion (PE), Pancreatic necrosis (PN), LDH, serum Calcium (Sca++), Pulse, GCS, MCTS1, Base deficit, Po2, BUN-24, and BUN-48 were significantly related(at 10% level of significance) with the severity of acute pancreatitis. Similarly out of 24, 10 parameters AST, LDH, Sca++, Pulse, PE, PN, Base deficit, MCTS1, Po2, and BUN 48were significantly covered more than 50% of the area in AUC analysis. Our proposed criteria based on 9 parameters LDH, Sca++, Pulse, PE, PN, Base deficit, MCTS1, Po2, and BUN 48which were blowing by the two methods (ANOVA and ROC). The sensitivity and specificity were higher with our proposed criteria 93.1% and 60.6%respectively as compared to the Ranson’s, modified Ranson, BISAP, and APACHE-II criteria. Conclusion: The newly proposed criteria for the assessment of the severity of AP is superior as compared to old criteria.